UPAYA KEPALA SEKOLAH MEMELIHARA MOTIVASI GURU: STUDI KUALITATIF DI MADRASAH TSANAWIYAH SWASTA KABUPATEN KUNINGAN - Muhammad Ridho Anwarul Sidik; Moh. Ali; Dewi Cahyani (Jurnal Manajemen Pendidikan, 2025)
This study aims to examine how principals in private Madrasah Tsanawiyah sustain and strengthen teacher motivation amid systemic pressures, limited resources, and increasing administrative demands. The research focuses on the roles of meaning-making, interpersonal relations, and ethical leadership in fostering teachers’ intrinsic motivation. A qualitative approach was employed using a multisite case study design involving three madrasahs located in both rural and urban areas of Kuningan Regency. Data were collected through in-depth interviews, participant observations, and document analysis. Thematic analysis revealed that teacher motivation does not rely on financial incentives but is grounded in professional meaning constructed through reflective dialogue, emotional support, and caring leadership practices. Principals act as “meaning guardians” by providing psychological safety, personal recognition, and moral presence. Teachers also demonstrate moral agency through subtle resistance to rigid administrative demands. This study proposes the Meaning-Based Motivation Model, which explains how ethical leadership, reflective dialogue, and professional narrative reconstruction shape intrinsic motivation within low-resource madrasahs. The model offers an alternative to performance-based management by emphasizing humanistic, relational, and moral dynamics of leadership.